Long‐term stoichiometry and fates highlight animal egestion as nutrient repackaging, not recycling, in aquatic ecosystems. (27th April 2017) - Halvorson, Halvor M.; Hall, Delaney J.; Evans‐White, Michelle A.
Summary: Animal defecation, or egestion, is a pronounced transformation of organic matter in many ecosystems. However, because egesta have been presumed recalcitrant and low nutrient, their significance and variability as an animal nutrient flux in aquatic settings – especially relative to mineralization via excretion – are poorly known. We compared carbon (C), nitrogen (N) and phosphorus (P) dynamics over short‐ to long‐term (up to 107 days) microbial decomposition of egesta from the aquatic shredders Allocapnia spp., Lirceus spp. and Tipula spp. fed low‐ or high‐P content Platanus occidentalis litter to investigate roles of egesta in aquatic nutrient dynamics. Tipula produced N and P deplete egesta of higher N : P compared to Lirceus and Allocapnia, and high‐P diets increased egesta P content compared to low‐P diets. Despite measurable C losses to decomposition, these differences in nutrient content persisted through decomposition, showing diet and species control both immediate and long‐term properties of egested particles. Egesta switched between uptake and release of dissolved phosphorus and ammonium during decomposition, and exhibited consistent net N uptake as nitrate–nitrite. Across species and diets, lower N : P egesta tended to exhibit greater uptake of dissolved inorganic N, suggesting P enrichment of egesta drove stronger dissolved N demand by decomposer microbes. Shredder egesta exhibit stable nutrient contents long term and, counter to assumptions that they are negligible or minor net sources, can be strong, extended sinks of dissolved inorganic nutrients. Future studies should consider contrasts between animal nutrient fluxes as excretion, which facilitates nutrient recycling via mineralization, vs. egestion, which slows nutrient recycling via organic nutrient repackaging and can create sinks of dissolved nutrients. A lay summary is available for this article. Abstract : Lay Summary